Reaksi Konsumen Pasca Belanja Produk Pakaian dan Kosmetik Secara Online di Instagram: Consumer Reactions After Shopping For Clothing and Cosmetic Products Online on Instagram - Khairunnisa Ismah; Sumarwan, Ujang; Nurhayati, Popong (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The development of online businesses, consumers still feel disappointed after shopping online as a consumer reaction after shopping online on Instagram. This study aims to analyze the factors that influence consumer reactions through consumer satisfaction after shopping for clothing and cosmetics products online on Instagram, and analyze consumer reactions after shopping for clothing and cosmetics products online on Instagram. Respondents used in the study were 200 respondents using purposive sampling with criteria; respondents have bought clothing or cosmetic products on Instagram in the last month. Data were analyzed using SEM-PLS. The results showed that service quality, product quality, and perceived value have a positive and significant effect on customer satisfaction in clothing and cosmetics products. Product quality, perceived value, and customer satisfaction have a positive and significant effect on consumer reactions on clothing products. Service quality, product quality, and customer satisfaction have a positive and significant effect on consumer reactions in cosmetic products. Consumer reactions after shopping for clothing and cosmetics products online on Instagram show that respondents agree with the subvariable statements of loyalty 1, loyalty 2, loyalty 3, paymore, switch, internal response, and external response, and have a significant effect between clothing and cosmetics products. Respondents disagree with the statement of external response subvariable 2 and there is no significant effect with external response subvariable 2. Keywords: clothing product, cosmetic product, consumer reaction, instagram, online shopping